Wednesday

April 16, 2014

April 16, 2014

Posted by **Joseph** on Friday, June 8, 2012 at 3:11am.

x0 mean initial value of x

same with v0

- physics -
**drwls**, Friday, June 8, 2012 at 4:03amAssuming that x0=0, a=2, and x=h,

h = v0*t + t^2

t^2 + v0*t -h = 0

t = [-v0 +/-sqrt(v0^2+4h)]/2

**Related Questions**

physics - A car traveling 56 km/h is 24 m from a barrier when the driver slams ...

Physics - def of average velocity = t^-1 (x - x0) (average velocity = t^-1(x-x0...

math - The forward difference formula can be expressed as : f'(x0) = (1/h)[f(x0+...

Math - extrapolation - The forward difference formula can be expressed as : f'(...

TO BOBPURSLEY - def of average velocity = t^-1 (x - x0) (average velocity = t^-1...

AP Physics - I'm trying to derive the formula v^2 = v0^2 + 2a(x-x0) were zeros ...

Physics - A car traveling 56 km/h is 24 m from a barrier when the driver slams ...

Physics PLEASE - I'm trying to derive the formula v^2 = v0^2 + 2a(x-x0) were ...

AP Physics - Hello I was trying to find the proof of the formula x = x0 + v0t +....

AP Physics - hi I need help on this proof ok I'm tyring to prove that v^2 = v^20...